Avaliação das vias colinérgica e nitrérgica no efeito antinociceptivo da corrente interferencial em modelo animal de dor inflamatória - Oliveira, Felipe Torres de (2019)
Introduction: Studies show the effectiveness of interferential current in reducing pain in various diseases. However, there is still a need for studies that highlight the physiological mechanisms by which analgesia is promoted by IC. The present work aims to investigate the central activation of cholinergic and nitrergic pathways by antinociceptive action of interferential current in animal model of joint inflammation. Material and methods: Thirty-six male Wistar rats were allocated to 6 groups, taking into consideration treatment and drugs or vehicles administered (control saline, CI + saline, L-arginine, bethanechol, CI + L-NNA and CI + atropine). For the nitrergic pathway, the drugs L-arginine and Nω-Nitro-L-arginine (L-NNA) were used. Cholinergic pathway was evaluated using atropine and bethanechol. All drugs and vehicles were administered intrathecally. Inflammation was induced in the left knee joint, and IC treatment was performed on the inflamed joint. The variables mechanical paw withdrawal threshold (PWT) and motor performance were analyzed at baseline, pre-treatment and post-treatment. Results: mechanical paw withdrawal threshold in all groups showed significant reduction after induction of joint inflammation (p <0.0001). In the intragroup analyzes between the pre and post-treatment moments, the CI + saline (p <0.0001), CI + L-NNA (p=0.0017), L-arginine (p = 0.0001) and bethanechol groups (p=0.0073) showed an increase in the threshold. Post-treatment intergroup comparison indicates that the control saline group threshold was significantly lower than the CI + saline (p=0.0014), CI + L-NNA (p=0.0010), L-arginine (p<0.0001) and bethanechol (p=0.0002). The CI + atropine and control saline groups were not significantly different after treatment. The values of the motor performance decreased significantly in all groups after induction. Comparing the pre and post-treatment moments, the CI + Saline (p=0.0303) and CI + L-NNA (p=0.0034) groups presented a reduction in the motor performance, but were not significantly different from the control saline group after treatment. The CI + saline group presented insignificant and very large effect size when compared, respectively, with the CI + L-NNA (d=0.04) and CI + atropine (d=1.68) groups after treatment. Conclusion: The results of the present study indicate that the antihyperalgesic effect of interferential current includes activation of spinal muscarinic receptors. Nitrergic pathway is not activated by the hypoalgesic action of the current.